Imperfection sensitivity of pyramidal core sandwich structures - Biagi, Russell; Bart-Smith, Hilary (International journal of solids and structures, 2007)
Lightweight metallic truss structures are currently being investigated for use within sandwich panel construction. These new material systems have demonstrated superior mechanical performance and are able to perform additional functions, such as thermal management and energy amelioration. The subject of this paper is an examination of the mechanical response of these structures. In particular, the retention of their stiffness and load capacity in the presence of imperfections is a central consideration, especially if they are to be used for a wide range of structural applications. To address this issue, sandwich panels with pyramidal truss cores have been tested in compression and shear, following the introduction of imperfections. These imperfections take the form of unbound nodes between the core and face sheets—a potential flaw that can occur during the fabrication process of these sandwich panels. Initial testing of small scale samples in compression provided insight into the influence of the number of unbound nodes but more importantly highlighted the impact of the spatial configuration of these imperfect nodes. Large scale samples, where bulk properties are observed and edge effects minimized, have been tested. The stiffness response has been compared with finite element simulations for a variety of unbound node configurations. Results for fully bound cores have also been compared to existing analytical predictions. Experimentally determined collapse strengths are also reported. Due to the influence of the spatial configuration of unbound nodes, upper and lower limits on stiffness and strength have been determined for compression and shear. Results show that pyramidal core sandwich structures are robust under compressive loading. However, the introduction of these imperfections causes rapid degradation of core shear properties.